2020
DOI: 10.1159/000512020
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Red Blood Cell and Platelet Transfusions and Retinopathy of Prematurity

Abstract: <b><i>Aim:</i></b> The aim of this study is to examine possible associations between the transfusion of RBC or platelets (PLTs) and the development of retinopathy of prematurity (ROP) in infants. <b><i>Methods:</i></b> This retrospective, national, case-control study included all live births in Switzerland between 2013 and 2018. We investigated preterm infants at a gestational age of &#x3c;28 weeks, who developed higher stage ROP (≥stage 2, <i>n</i&g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 25 publications
2
27
1
Order By: Relevance
“…The number of subjects with ROP are equally divided within the birth weight category with 11 subjects weighing < 1500 g and 11 subjects weighing ≥ 1500 g. Most of the patients with ROP were on oxygen therapy for ≥ 7 days, similar to the findings of a study conducted in Jakarta (18), but opposing to a report by Hakeem et al (19) Out of 22 patients with ROP, only 5 received RBC transfusion. This result is in line with a study by Rao et al (20) and opposite of a report by Hengartner et al (21) Almost all of the patients with ROP were born by caesarean section and only one patient was born spontaneously. This result is in accordance with a research by Dewi et al (22) Most of the case group subjects were born single, similar to the findings of previous studies (13,23) and in contrast with a study by Akkawi et al (24) Preterm birth is defined as a live birth before the gestational age reaches a full 37 weeks.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The number of subjects with ROP are equally divided within the birth weight category with 11 subjects weighing < 1500 g and 11 subjects weighing ≥ 1500 g. Most of the patients with ROP were on oxygen therapy for ≥ 7 days, similar to the findings of a study conducted in Jakarta (18), but opposing to a report by Hakeem et al (19) Out of 22 patients with ROP, only 5 received RBC transfusion. This result is in line with a study by Rao et al (20) and opposite of a report by Hengartner et al (21) Almost all of the patients with ROP were born by caesarean section and only one patient was born spontaneously. This result is in accordance with a research by Dewi et al (22) Most of the case group subjects were born single, similar to the findings of previous studies (13,23) and in contrast with a study by Akkawi et al (24) Preterm birth is defined as a live birth before the gestational age reaches a full 37 weeks.…”
Section: Discussionsupporting
confidence: 90%
“…Infants who received RBC transfusion have 1.09 times (95% CI 0.343-3.480) higher odds for the occurrence of ROP compared to those who never received red blood cell transfusion. Badriah et al (18) and Hengartner et al (21) who previously conducted a study in Indonesia and Switzerland respectively reported similar findings where RBC transfusion is not related to the development of ROP (p=0.327, p=0.179). In contrast, two previous studies reported significant relation between red blood cell transfusion and retinopathy of prematurity.…”
Section: Discussionmentioning
confidence: 60%
“…The primary outcome was a composite of death, BPD, NEC, or ROP. This composite outcome was selected on the basis of the importance of these outcomes to the risk of long-term neurodevelopmental impairment, 22 , 23 the role of oxidant stress and/or inflammation in the pathogenesis of these diseases, 24 and prior studies 10 , 25 , 26 , 27 reporting potential associations between RBC transfusion and an increased risk of components of the composite outcome. In addition, a similar composite outcome was used in a prior trial comparing neonatal transfusion thresholds.…”
Section: Methodsmentioning
confidence: 99%
“…During the development of ROP, the expression of hypoxia-related factors increases abnormally. 21 , 22 Studies with OIR mice have indicated that during retinal angiogenesis, hypoxia causes cells to undergo oxidative stress, leading to cell apoptosis, which affects inflammation and leads to pathological changes in the retinal blood vessels. 23 26 The lncRNA TUG1 is widely expressed in normal mammalian tissues.…”
Section: Discussionmentioning
confidence: 99%